Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma Presenting as Chronic Diarrhea; An Unusual Presentation of a Common Lymphoproliferative Disorder - Smitha Narayana Gowda; Hafez Mohammad Abdullah; Rakshya Sharma; Mohamed A. Abdallah (Case Reports in Gastrointestinal Medicine)
Chronic lymphocytic leukemia (CLL) is the most common lymphoproliferative disorder in the United States. It has a variable presentation with most patients having asymptomatic lymphocytosis. Many other patients present with lymphadenopathy or enlargement of other organs of the reticuloendothelial system. However, CLL can present with extramedullary involvement. Most commonly, this is in the form of skin or central nervous system involvement, though rarely it can present with gastrointestinal involvement. Here, we present the case of a 70-year-old Caucasian male who presented with chronic diarrhea for over 4 months. After failing conservative treatment, a colonoscopy was performed which showed diffuse mucosal nodularities with a biopsy revealing CLL. The patient was treated successfully with chemotherapy and his diarrhea improved. This is a differential to keep in mind in patients with chronic diarrhea, once the more common causes have been ruled out.